The Effectiveness of Using Memrise Application in Improving Students’ Speaking Skills - Satrianto, Faiz; Tusino, Tusino; Nugraeni, Ismawati Ike (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study applied a quantitative approach with a quasi-experimental design for data collection. A total of 64 students were involved in the study, and data were obtained through pre- and post-tests using the Memrise application. The results of the t-test analysis showed a significance value of 0.005 (p < 0.05), indicating that the observed differences were statistically significant and not due to chance. There was a significant difference (p < 0.05) between the experimental group and the control group, indicating that the use of the Memrise application in learning can improve students' speaking skills more effectively than traditional methods. Furthermore, the results of this study prove that technology-supported language learning not only contributes to improving students' cognitive aspects but also has a positive effect on their motivation and affective aspects, which is crucial in the development of speaking skills. This finding also emphasises that technology in language learning has a significant influence on students' cognitive aspects and motivation, which is very important in the study of speaking skills.